PENGARUH METODE MASERASI DAN METODE SOXHLETASI TERHADAP KADAR FENOLIK TOTAL DAN AKTIVITAS ANTIOKSIDAN DAUN NANGKA (Artocarpus heterophyllus L.) - Robby Najini; Sri Wahdaningsih (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Jackfruit (Artocarpus heterophyllus L.) is a plant native to Southeast Asia that can grow in tropical climates such as Indonesia. Jackfruit leaves contain various secondary metabolite compounds, including phenols which can have antioxidant activity. The extraction method of a plant can affect the amount of compounds in the extract. This study aims to compare the maceration and soxhletation extraction methods on the antioxidant activity and total phenolic content of jackfruit leaves. Next, these two types of extracts will be tested for antioxidant activity using the DPPH method and then the total phenolic content will be determined using the Folin Ciocalteu method. The results of measuring the total phenolic content in the ethanol extract of jackfruit leaves using the maceration method were 0.004528 mg GAE/g while the ethanol extract of jackfruit leaves using the soxhletation method was 0.004252 mg GAE/g. The antioxidant value was measured based on the lC50 value obtained from the maceration method of 336.59 µg/mL and the soxhletation method obtained an lC50 value of 354.31 µg/mL.